Role of C‒H bond in the antioxidant activities of rooperol and its derivatives: A DFT study. (October 2020) - Zheng, Yan-Zhen; Fu, Zhong-Min; Deng, Geng; Guo, Rui; Chen, Da-Fu
Abstract: Rooperol and its derivatives, derived from the Hypoxis rooperi plant, are polyphenolic and norlignan compounds with excellent antioxidant activities. The reaction enthalpies for the free-radical scavenging by rooperol and its six derivatives were studied using density functional theory. We found that the C−H groups played a significant role in the antioxidant activities in non-polar phases. In the gas and benzene phases, rooperol and its derivatives preferentially underwent the free-radical scavenging process via the 3‒CH group by following the hydrogen atom transfer (HAT) mechanism. In polar phases, the sequential proton loss electron transfer (SPLET) was the most preferred mechanism, and the phenolic O‒H groups played a significant role. Additionally, we found that when the hydrogen atom in the OH group was replaced by a glucose moiety, the antioxidant activity of the adjacent OH group was reduced. ROP, DHROP-I, DHROP-II, ROP-4″-G and ROP-4′G have catechol moiety, they may proceed double step-wise mechanisms to trap free radicals. In the gas and benzene phases, the preferable mechanism is dHAT. In water phase, it is SPLHAT. Graphical abstract: The preferred free radical scavenging mechanism of rooperol and its derivatives in different phases. Image 1 Highlights: Antioxidative mechanisms of rooperol and its derivatives were analysed. The lowest energy conformers were stabilized by the intramolecular hydrogen bonds. C−H group played vital role in the antioxidant activity in non-polar phases. In polar phases, the O‒H groups played non-negligible roles. The preferred mechanisms vary among the different phases.